2018
DOI: 10.15406/jdhodt.2018.09.00382
|View full text |Cite
|
Sign up to set email alerts
|

Oral health findings, needs and demands of visually impaired children in Saudi Arabia

Abstract: | http://medcraveonline.com only 8% of people have a congenital visual impairment with the rest developing a visual impairment through local or systemic disease, accidents or age-related degeneration. 2 Furthermore, a huge proportion of adults with a visual impairment relate to hearing problems which may require further help to the provision of dental care. 3 Some of the causes of visual impairment may be associated with other medical problems, such as cardiac defects or diabetes, which are more likely to take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…On being asked whether rinsing after meal,90 (69.2%) visually impaired students said they did, 39 (30%) did seldom and 1 (0.8%) never rinsed after meal (Table 3). Azrina et al, 1 Alghamdi et al, 8 and Mohd-Dom et al 9 The present study reported that majority of them cleaned their teeth by using toothbrush where similar to the same population as reported by Ameer et al 4…”
Section: Resultssupporting
confidence: 85%
“…On being asked whether rinsing after meal,90 (69.2%) visually impaired students said they did, 39 (30%) did seldom and 1 (0.8%) never rinsed after meal (Table 3). Azrina et al, 1 Alghamdi et al, 8 and Mohd-Dom et al 9 The present study reported that majority of them cleaned their teeth by using toothbrush where similar to the same population as reported by Ameer et al 4…”
Section: Resultssupporting
confidence: 85%
“…The findings highlighted improper tooth brushing on the majority of the participants even though they were educated; completing at least secondary school. In addition, many visually impaired individuals found maintaining their oral hygiene more difficult due to their lack of vision which is a constraint to understanding and mastering techniques of oral hygiene practices [ 30 ]. Visual disorders affect oral health due to physical, social, or informational barriers related to impairment, medical condition, or a lack of customized information [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of dental caries in visually impaired people refers to inadequate plaque removal which may be attributed to lack of cleaning habits, healthy diet, eating pattern, physical limitations, medication and attitudes of parents and caregivers [3 -7]. Visual disorders affect oral health due to physical, social, or informational barriers related to impairment, medical condition, or a lack of customized information [8]. People with visual disorders cannot visualize plaque on their teeth surfaces which makes it difficult for them to understand the importance of oral hygiene, which results in the progression of dental caries as well as periodontal diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Attitude modifications for visually impaired individuals, their parents and caregivers are one of the most important ways to improve oral health for those patients. Diet counseling, dental health education and preventive procedures, plaque removal instruction, frequency and timing of oral hygiene procedures, dental health education, and audio-tactile performance techniques are other aspects of improving oral health status for individuals with visual impairment [8].…”
Section: Introductionmentioning
confidence: 99%